Ativismo judicial no Brasil e as consequências de sua consolidação - Oliver, Luciana Zanchetta (2016)
The goal of this study is to question the consolidation of judicial activism in Brasil verifying if the decisions made by the courts are in accordance to the constitution and modern social values. For that, we need to verify the limits of the judiciary power based on constitutional principles, the separation of powers and democratic ideals. This dissertation points out that the activism is pertinent and consolidated, once the Judiciary Power is accountable for ceasing omission, evaluating and correcting the mistakes made by the Legislative and Executive powers when they occur. The research shows that despite the legality of the activism, it must be applied with responsibility and moderation protecting social rights and equally protecting the Democratic State